Scaling Switching-Sequence-based Control for Networked Power Converters - Roig Greidanus, Mateo D.; Mazumder, Sudip K.; Chatterjee, Debanjan; Tahir, Muhammad; Gajanur, Nanditha (IEEE access, 2023)
The control of networked power-electronics systems (PESs) using predictive switching sequences has been described in this paper. The switching-sequence-based control (SBC), first introduced in [1], applies converter switching sequences to an optimization cost function to be satisfied under stability bounds. To evaluate the SBC control scalability and efficacy, the control strategy is implemented for centralized and distributed network architectures for different PES topologies. Given the two network architectures, dynamic and steady-state performances obtained using SBC are discussed using two different case illustrations: for a standalone and network of parallel hybrid active neutral-point-clamped (H-ANPC) inverters; and for a standalone and network of parallel differential-mode Cuk rectifiers (DMCRs). Hence, the work highlights the feasibility of extending the SBC control application to PESs networks subject to communication constraints and latency dependencies.